2015
DOI: 10.18268/bsgm2015v67n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Patrimonio natural de la Reserva Ecológica del Pedregal de San Ángel y áreas cercanas: sitios de interés geológico y geomorfológico al sur de la Cuenca de México

Abstract: 227 ResumenLa Reserva Ecológica del Pedregal de San Ángel (REPSA) es un territorio de conservación creado en 1983 dentro del campus de la Universidad Nacional Autónoma de México (UNAM). El objetivo de la REPSA es conservar un espacio de alto valor biológico y cultural, único en su género por la diversidad y características de la biota que sostiene, y que contiene los últimos reductos de ecosistemas naturales del sur de la Cuenca de México. Además del interés en los aspectos biológicos, la REPSA es un espacio g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Mexico City is among the top five megacities of the world with respect to total human population [34]. Within this megacity, an ecological reserve (Reserva Ecológica del Pedregal de San Ángel, REPSA) was created in 1983, as an effort to preserve a unique xerophytic scrub that was formed after the eruption of the Xitle volcano almost 2 000 years ago [35–37]. Its 237 hectares are currently inhabited by 1 849 native species of plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Mexico City is among the top five megacities of the world with respect to total human population [34]. Within this megacity, an ecological reserve (Reserva Ecológica del Pedregal de San Ángel, REPSA) was created in 1983, as an effort to preserve a unique xerophytic scrub that was formed after the eruption of the Xitle volcano almost 2 000 years ago [35–37]. Its 237 hectares are currently inhabited by 1 849 native species of plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…The REPSA is now home to 1,849 native and 317 exotic species (REPSA, 2017). As other PUGS, this area is inserted in an urban matrix and provides ecosystem services such as highwater infiltrations to the city and flood regulation (Vargas, 1984;Delgado et al, 1998;Nava-López et al, 2009;Palacio-Prieto and Guilbaud, 2015).…”
Section: Study Sitementioning
confidence: 99%
“…Previous studies on Mexico City´s geoheritage have focused on Xitle volcano because it is the youngest dated volcano of the SCVF (1670 +/-35 calibrated years before present; Siebe 2000) and hence one of the best preserved, and it fed an extensive lava field now covered by the city, therefore having a strong connec-tion with the urban communities (Figure 1). Those studies have identified main geosites that have great scientific and cultural significance and provide numerous ecosystem services (Palacio and Guilbaud 2015;Guilbaud et al 2021;Nieto-Torres et al 2022). Nevertheless, many other public parks within the city also contain remains of this geoheritage, and the development of research projects in these parks could allow to advance the scientific knowledge while at the same time allow scientists to engage with citizens and stakeholders, with the aim to contribute to environmental conservation, increase people´s resilience to volcanic hazards, and reduce the science-society gap (Topp et al 2018(Topp et al , 2020Sarkki et al 2020;Lièvre et al 2022).…”
Section: Introductionmentioning
confidence: 99%